Investigation of electrochromic performances of multicolor V2O5 devices fabricated at low processing temperature - Ming-Yue Tan; Gregory Soon How Thien; Kar-Ban Tan; H. C. Ananda Murthy; Kah-Yoong Chan (Scientific Reports)
Abstract In recent decades, poorly insulated windows have increased the energy consumption of heating and cooling systems, thus contributing to excessive carbon dioxide emissions and other related pollution issues. From this perspective, the electrochromic (EC) windows could be a tangible solution as the indoor conditions are highly controllable by these smart devices even at a low applied voltage. Literally, vanadium pentoxide (V2O5) is a renowned candidate for the EC application due to its multicolor appearance and substantial lithium insertion capacity. Despite the growing interest in V2O5 thin films, only limited literature study is available for V2O5 films specifically the annealing effects of these films at lower temperatures (< 300 °C). It is noteworthy that a low temperature is advantageous for glass-based EC devices, as it prevents deformation, cracking, and structural damage to the transparent conductive glass. In this study, V2O5 thin films were fabricated using the sol–gel spin coating technique prior to annealing over the temperature range of 100–300 °C. Subsequently, V2O5 thin films were assembled into a device form to analyze their EC characteristics. The V2O5 device, featuring thin film annealed at 200 °C, demonstrated excellent EC performance with high optical contrast of 42.32%, high coloration efficiency (CE) of 34.93 cm2/C, as well as rapid coloring and bleaching times of 0.4 s and 3 s, respectively. These results shed light on the importance of annealing temperature control towards the EC performance of V2O5 devices for future applications.